Risk factors for peripheral venous catheter-related phlebitis stratified by body mass index in critically ill patients: A post-hoc analysis of the AMOR-VENUS study - Kashiura, Masahiro; Yasuda, Hideto; Oishi, Takatoshi; Kishihara, Yuki; Moriya, Takashi; Kotani, Yuki; Kondo, Natsuki; Sekine, Kosuke; Shime, Nobuaki; Morikane, Keita (Frontiers in Medicine, 2022)
Introduction Phlebitis is an important complication in patients with peripheral intravascular catheters (PIVCs). Although an association between body mass index (BMI) and phlebitis has been suggested, the risk of phlebitis according to BMI has not been well elucidated. Therefore, in this study, we analyzed the risk of phlebitis according to BMI in patients in the intensive care unit (ICU). Materials and methods This study undertook a secondary analysis of the data from a prospective multicenter observational study assessing the epidemiology of phlebitis at 23 ICUs in Japan. Patients admitted into the ICU aged ≥18 years with a new PIVC inserted after ICU admission were consecutively enrolled and stratified into the following groups based on BMI: Underweight (BMI < 18.5 kg/m2), normal weight (18.5 ≤ BMI < 25.0 kg/m2), and overweight/obese (BMI ≥ 25.0 kg/m2). The primary outcome was phlebitis. The risk factors for phlebitis in each BMI-based group were investigated using a marginal Cox regression model. In addition, hazard ratios and 95% confidence intervals were calculated. Results A total of 1,357 patients and 3,425 PIVCs were included in the analysis. The mean BMI for all included patients was 22.8 (standard deviation 4.3) kg/m2. Among the eligible PIVCs, 455; 2,041; and 929 were categorized as underweight, normal weight, and overweight/obese, respectively. In the underweight group, catheter size ≥ 18 G and amiodarone administration were independently associated with the incidence of phlebitis. Drug administration standardization was associated with the reduction of phlebitis. In the normal weight group, elective surgery as a reason for ICU admission, and nicardipine, noradrenaline, and levetiracetam administration were independently associated with the incidence of phlebitis. Heparin administration was associated with the reduction of phlebitis. In the overweight/obese group, the Charlson comorbidity index, catheter size ≥ 18 G, and levetiracetam administration were independently associated with the incidence of phlebitis. Catheters made from PEU-Vialon (polyetherurethane without leachable additives) and tetrafluoroethylene were associated with the reduction of phlebitis. Conclusion We investigated the risk factors for peripheral phlebitis according to BMI in ICU and observed different risk factors in groups stratified by BMI. For example, in underweight or overweight patients, large size PIVCs could be avoided. Focusing on the various risk factors for phlebitis according to patients’ BMIs may aid the prevention of phlebitis.